Interfaith Marriage from a Legal Justice Perspective After The Supreme Court’s (SEMA) 2023 Circular Letter - Ahmad Faiz Shobir Alfikri; Rahmatullah, M. Azam (Alauddin Law Development Journal, 2024)
Supreme Court Circular Letter No. 2 of 2023 aims to ensure unity and legal certainty in interfaith marriage. This study used normative methodology. The results showed that from a juridical standpoint, it holds legal recognition and binding force under Law 12/2011 and the Supreme Court Law. Sociologically, it aligns with prevailing social realities. Philosophically, its establishment seeks to foster legal unity and certainty. However, its implementation falls short of optimal due to incomplete fulfillment of legal justice aspects, particularly regarding legal certainty per Gustav Radbruch’s perspective and requires evaluation through John Rawls’ justice principles, particularly concerning equality.